Plasmablastic lymphoma presenting as a brachial artery aneurysm associated with haemodialysis arteriovenous access ligation in a renal transplant patient. Issue 1 (January 2020) - Franchin, Marco; Amaglio, Cristina; Cervarolo, Maria Cristina; Piffaretti, Gabriele; Uccella, Silvia; Iovino, Domenico; Ietto, Giuseppe; Carcano, Giulio; Tozzi, Matteo
Introduction: Plasmablastic lymphoma is a rare and aggressive neoplasm, generally associated with immunodeficiencies and related to latent Epstein-Barr virus infection. This case is the first reported case of plasmablastic lymphoma relapse in aneurysmatic brachial artery wall. Case description: We describe the case of male patient who underwent cadaveric donor kidney transplant when he was 61 years old and radio-cephalic distal arteriovenous fistula ligation 8 months later. After 8 years, he developed gingival plasmablastic lymphoma treated with cyclophosphamide, hydroxydaunorubicin, oncovin and prednisone regimen with subsequent remission. During follow-up, a mid-forearm vascular access was created because of the worsening of renal function. Twenty-two months later, the patient showed a symptomatic 20 mm brachial artery aneurysm with radiological signs of imminent rupture, for which he was surgically treated. The histological evaluation of the brachial artery specimen revealed a relapse of plasmablastic lymphoma in the arterial wall and in an adjacent lymph node. Conclusion: Brachial artery aneurysms are a rare complication in kidney transplant recipients after ligation of arteriovenous access for haemodialysis. Here, we report a case in which this condition is associated with an even rarer plasmablastic lymphoma. A common aetiology, due to immunosuppressive therapy, is postulated for the two coexisting diseases.